Smart Engagement and Smart Urbanism: Integrating “The Smart” Into Participatory Planning and Community Engagement - Jung, Jin-Kyu (2023)
The smart city epitomizes a new paradigm shift in urban planning, policy, and cities. Smart cities require and are powered by smart city principles to succeed, including smart technologies, smart infrastructure, and smart governance; however, they also need to engage closely with the citizens who are most affected by the deployment of the smart city and who also embrace the diverse perspectives, experiences, and opportunities of living in smart cities, i.e., smart engagement. What would be forms of collaborative democracy and inclusive citizen participation in smart city planning? To what extent can smart city planning respond and address inequality, justice, and social and digital division? How can we create community-based climate change planning with the smart? What would be a smart community platform that supports smart engagement, and how do cities around the world establish smart city policy and assess the impact on smart engagement? This thematic issue aims to answer these questions by exploring new visions, facets and methods, practices, and tools for enabling smart engagement. Drawing on research from various countries and cities across the world, the contributions bring new prospects of smart engagement and smart urbanism and illuminate how the theory, plan and policy, and practices of smart engagements are binding to the extent of citizen participation and engagement in smart cities.